2021
DOI: 10.1093/nutrit/nuab033
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet promotes hypothalamic inflammation in animal models: a systematic review

Abstract: Context Hypothalamic inflammation and dysfunction may be induced by high-fat diets. However, the mechanisms involved in this process have not been fully elucidated. Objective To evidence, in animal models, of how a high-fat diet influence the mechanisms involved in hypothalamic inflammation. Data sources Scopus, PubMed/Medline, Web of Science, Science Direct,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A great deal of research indicated that the intake of food with a high percentage of calories from fat negatively affects energy balance of the organisms (Hill et al., 2012; Linehan et al., 2018; Santos et al., 2022; Shah & Garg, 1996; Sun et al., 2008). In our study, stronger responses to CCK were observed at night, but this significant daily difference disappeared in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of research indicated that the intake of food with a high percentage of calories from fat negatively affects energy balance of the organisms (Hill et al., 2012; Linehan et al., 2018; Santos et al., 2022; Shah & Garg, 1996; Sun et al., 2008). In our study, stronger responses to CCK were observed at night, but this significant daily difference disappeared in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…We did not see these inflammatory changes in the long-term HFD study. Mice fed a high-fat diet display chronic hypothalamic inflammation [45,46]. BDNF-TrkB is involved in regulating neuroinflammation [47,48].…”
Section: Plos Onementioning
confidence: 99%
“…Importantly, both programmed mechanisms of aging and stochastic processes contributing to the genesis aging phenotypes are impacted by nutrition and diets (e.g., caloric restriction confers multifaceted anti-aging effects) [ 93 , 94 ]. There is strong evidence that unhealthy diets (e.g., a high fat diet, Western diets, and methionine-rich diets), because of accelerated cellular aging, exacerbate the development of age-related diseases and shorten lifespan in laboratory animals [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Development of aging phenotypes and the pathogenesis of age-related diseases are also influenced by a heightened state of low-grade sterile systemic inflammation (“inflamm-aging”) [ 105 ].…”
Section: Cellular and Molecular Mechanisms Of Aging: Regulation By Nu...mentioning
confidence: 99%
“…Recent findings highlight the association between inflammation and deleterious frailty status in older adults [ 106 , 107 ]. Inadequate diets (e.g., a high fat diet [ 95 , 96 , 97 , 98 , 99 ], diabetogenic diets, high methionine diets [ 108 , 109 , 110 ]) are an important contributing factor to this low-grade systemic inflammation, but it is also one of the easiest modifiable interventions for elderly individuals to intervene on the process of aging [ 105 ]. Preclinical studies have developed a wide range of dietary interventions to delay aging and prevent development of age-related diseases in laboratory animals.…”
Section: Cellular and Molecular Mechanisms Of Aging: Regulation By Nu...mentioning
confidence: 99%